Small is beautiful: the important role of small copepods in carbon budgets of the southern Benguela upwelling system. (9th November 2022) - Bode-Dalby, Maya; Würth, Randi; de Oliveira, Lívia Dias Fernandes; Lamont, Tarron; Verheye, Hans M; Schukat, Anna; Hagen, Wilhelm; Auel, Holger
Abstract: Small copepod genera play an important role in marine food webs and biogeochemical fluxes but have been neglected in many studies. This is the first study determining biomass, carbon consumption and egestion rates of small- (<1 mm prosome length, PL), medium- (1–1.5 mm PL) and large-sized (>2 mm PL) copepods along a cross-shelf transect in the southern Benguela upwelling system. Calanoids contributed on average 55 ± 19% to total copepod abundance and 82 ± 13% to total copepod biomass. Small-sized Oithona spp. (114–119 mg C m −2 d −1 ) and Clausocalanidae/Paracalanidae (87–263 mg C m −2 d −1 ) as well as large-sized Calanoides natalis (47–193 mg C m −2 d −1 ) were the dominant consumers at the most inshore stations. Small- and medium-sized copepodite stages of Metridia lucens were also important, especially towards the continental slope. At offshore stations, Clausocalanidae/Paracalanidae, Oithona spp., Pleuromamma spp., Calanus agulhensis, Acartia spp., C. natalis and M. lucens were dominant consumers. Hence, usually small- and medium-sized copepods dominated total copepod ingestion and egestion, emphasizing that inadequate representation of small copepods will lead to significant underestimations and misinterpretations of the functioning of zooplankton communities and finally to inadequate biogeochemical models.